Novel approach of determining the best absorbent for the quantification of aqueous analyte using laser-induced breakdown spectroscopy (LIBS): Zeolite versus bentonite - Ahmad, Khairunnas; Prasetyo, Siswoyo; Zaitun, Zaitun; Hajashafira, Ceudah (Narra Sains Indonesia, 2024)
Heavy metal pollution, particularly from sources like lead (Pb), poses significant risks to human health and the environment. Monitoring heavy metal contamination is essential, and laser-induced breakdown spectroscopy (LIBS) is a promising technique for this purpose. However, matrix effects, particularly from adsorbent materials like zeolite and bentonite, can influence the accuracy of LIBS measurements. This study aims to investigate the matrix effects of zeolite and bentonite on the measurement of Pb using LIBS. It is focusing on how the physical and chemical properties of these materials impact the detection of Pb emission lines. Zeolite and bentonite samples were prepared by grinding and sieving to obtain powders with particle sizes less than 74 µm. These powders mixed with varying weights of lead nitrate (Pb(NO3)2) and pelletized to create uniform samples. The pellets were analyzed using LIBS, employing a Q-switched Nd:YAG laser. The emitted plasma light was collected and transmitted to a spectrometer equipped with an intensified charge-coupled device (ICCD) camera. The spectral data were accumulated over 10 laser shots to ensure accuracy in detecting the elemental composition. The study found the matrix effects from bentonite and zeolite have significant influence on the intensity and clarity of Pb emission lines. Matrix effects on bentonite indicated a stronger influence on Pb detection compare to zeolite. It mainly due to the presence of Fe and Ti, which is affected the Pb I lines at 405.8 nm and 368.3 nm. In contrast, zeolite exhibited fewer interferences, but the matrix effect was still obvious. These matrix effects-derived interreferences can be associated with the physical and chemical properties of the adsorbents. Further research into different adsorbents and their matrix effects is warranted to improve the accuracy of LIBS in heavy metal analysis.